Peer evaluation and its blurred boundaries : results from a meta-evaluation in initial vocational education and training - Speer, Sandra [Verfasser] (My University, 2010)
"Peer evaluation has proved to be a popular approach with both peers and the evaluated, but there has been considerable variation in the ways in which peer evaluations have been implemented. There are different forms, purposes and ways of organizing peer evaluation. Peer evaluations are also not uniform and links to other evaluations can be made. After providing a general overview of different kinds of peer evaluation, this article focuses on the results from a meta-evaluation of peer evaluation in Initial Vocational Education and Training (IVET). This meta-evaluation was partly inspired by existing evaluation standards and covered fifteen peer-review pilots in eight European countries. First, the scope of the peer team and the underlying evaluative framework are discussed. Second, the nuances of implementation and the conflicts that exist are highlighted. The article concludes that, under certain conditions, peer evaluation and self-evaluation provide a powerful tandem to produce empirically grounded, context-sensitive information to support school improvement." (Autorenreferat, BIBB-Doku)
Keywords: L 6.2.3 Evaluation; S 1.3 Berufliche Erstausbildung; I 2.2 Europa; Wirkungsforschung; Evaluation; Peer Review; Methodologie; Wissenschaftliche Begleitung; Berufsausbildung; Europa